2007
DOI: 10.1097/mbp.0b013e3280b08317
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure determination by traditionally trained personnel is less reliable and tends to underestimate the severity of moderate to severe hypertension

Abstract: A total of 907 participants were enrolled. More than 99% of both systolic and diastolic TT nurse BP ended with zero, demonstrating that they had terminal digit preference. ST nurse BP was in better agreement with digital blood pressure measurement than with TT nurse BP. The number of differences of < or =5 mmHg between ST nurse BP and digital blood pressure measurement was approximately 60% for both systolic and diastolic blood pressure. Overall, traditionally trained nurses overestimated, rather than underest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…Roubsanthisuk et al demonstrated a higher terminal digit preference of zero among untrained health care providers (8). Our data on EMS personnel are consistent with the observation that health care providers tend to measure blood pressures in deciles despite the fact that this introduces error into the measurement.…”
Section: Discussionsupporting
confidence: 91%
“…Roubsanthisuk et al demonstrated a higher terminal digit preference of zero among untrained health care providers (8). Our data on EMS personnel are consistent with the observation that health care providers tend to measure blood pressures in deciles despite the fact that this introduces error into the measurement.…”
Section: Discussionsupporting
confidence: 91%
“…A possible limitation of our study is that we relied on lay trained non-clinician interviewers for the measurement of blood pressure. Data suggest that trained personnel actually underestimate the prevalence of hypertension as compared with clinicians 40 . Our classification of hypertension was based on an average of two measurements and not on more regular monitoring.…”
Section: Discussionmentioning
confidence: 96%
“…Studies show that similar automated wrist devices to measure blood pressure compare well with gold-standard measurements using sphygmomanometers and trained health personnel 13 , 40 . A possible limitation of our study is that we relied on lay trained non-clinician interviewers for the measurement of blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Variability inherent in the subject and/or construct being assessed may have contributed to inconsistent measurement. One of the greatest challenges in assessing reliability occurs when measuring a response that is inherently unstable (Roubsanthisuk, Wongsurin, Saravich, and Buranakitjaroen, 2007). Reliability examinations for the current study were performed within 24-48 h after the initial examination and prior to beginning treatment.…”
Section: Discussionmentioning
confidence: 99%